2014
DOI: 10.14419/ijsw.v2i1.2275
|View full text |Cite
|
Sign up to set email alerts
|

Haematological changes in Trypanosoma evansi infected cattle

Abstract: During the three years period of study twelve cross bred cattle were identified that they were suffering with clinical Trypanosomiasis. Up on clinical examination cattle had anorexia, fever, ocular discharges, dullness and enlarged lymph nodes. Stained peripheral blood examination revealed the presence of Trypanosoma evansi. Haematological abnormalities include decreased TEC, PCV, Hb and TLC values (P<0.01). The present leucopaenia was characterized by neutrophilia, eosinophilia and lymphocytopaenia (P>0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
5
14
0
Order By: Relevance
“…Hypophosphataemia in the present case may be due to inadequate supplement of phosphorous. In this study observed signs in accordance with the (Muhammad et al 2001 Recorded haematological parameters were deviated from the apparently healthy animals in our local areas (Sivajothi et al 2014b;Reddy et al 2014b). Decreased haemoglobin concentration, haematocrit and erythrocyte count indicative of anaemia.…”
Section: Treatment and Discussionsupporting
confidence: 91%
“…Hypophosphataemia in the present case may be due to inadequate supplement of phosphorous. In this study observed signs in accordance with the (Muhammad et al 2001 Recorded haematological parameters were deviated from the apparently healthy animals in our local areas (Sivajothi et al 2014b;Reddy et al 2014b). Decreased haemoglobin concentration, haematocrit and erythrocyte count indicative of anaemia.…”
Section: Treatment and Discussionsupporting
confidence: 91%
“…Observed haematological parameters under the normal range of local values recorded in the previous studies (Sivajothi et al 2014b). Faecal samples and whole blood did not reveal any parasitic ova and haemoprotozoan diseases respectively.…”
Section: Resultsmentioning
confidence: 54%
“…Trypanosomosis ranks high in importance amongst animals due to its devastating effects on the livestock health leading to severe economic losses to the dairy industry (Laha et al 2008). Trypanosoma evansi causes anaemia, leucopaenia, abnormal changes in serum biochemical parameters and histopathological changes in experimental and natural infections (Sivajothi et al 2013a(Sivajothi et al , 2014a(Sivajothi et al , 2014b. Diagnosis of trypanosomes by direct parasitological techniques is not reliable, especially for naturally occurring field cases, where parasitaemia is often low and sporadic.…”
Section: Introductionmentioning
confidence: 99%